First Record of Cheiloneurus clαviger (Thomson) (Hymenoptera: Encyrtidae) on Corfu Island - Macropodi, M.V.; Viggiani, G. (ENTOMOLOGIA HELLENICA, 1998)
During an ongoing research programme on Saissetia oleae (Oliv.) (Homoptera: Coccidae) and its parasites on the island of Corfu, the presence of the hyperparasite Cheiloneurus clαviger (Thomson) (Hymenoptera: Encyrtidae) was recorded, for the first time, in samples of parasitized Saissetia oleae in 1991. The identification of C. clagiver was made by the junior author. The adults of Cheiloneurus clαviger emerged from S. oleae females parasitized by Metaphycus lounsburyi (How.) (Hymenoptera: Encytridae), after they were placed in plastic capsules. Tables 1 and 2 give the number of adults of S. oleae, C. claviger and M. lounsburyi that emerged from S. oleae at two experimental fields. M. lounsburyi is one of the main parasitoids of S. oleae acting as an internal parasite of the fourth larval instar. The numbers of C. claviger emerged were very low compared with the numbers of M. lounsburyi, indicating that at present C. claviger is not a serious limiting factor for the population of M. lounsburyi. The presence of a group of coarse bristles at the apex of the scutellum and the long marginal vein of fore wings are the peculiarities of the genus Cheiloneurus. The incomplete infuscation of the fore wings and the colour of the antennae with only the 5th funicular segment blackish can easily allow the discrimination of C. claviger females from those of congeneric species. Cheiloneurus clαviger is reported as a hyperparasitoid of several coccids of economic impor tance mainly via other encyrtid parasitoids. In Italy, C. claviger has been found to act as a hyperparasite of Kermesidi (genus Kermes) which infest Pinoideae. Previous reports on the entomophagous fauna of S. oleae on Corfu do not include C. claviger and it is assumed that the hyperparasitoid has been introduced rather recently. The actual role oil the parasitic complex of S. oleae and the distribution of this hyperparasite on the island should be further investigated.